Real‐world outcome with abiraterone acetate plus prednisone in Asian men with metastatic castrate‐resistant prostate cancer: The Singapore experience. Issue 1 (11th November 2019) - Chan, Johan; Yap, Shi Yin; Fong, Yian Ching; Lim, Heng Chi; Toh, Chee Keong; Ng, Quan Sing; Rajasekaran, Tanujaa; Chua, Melvin; Lee, Lui Shiong; Wong, Alvin; Loh, Ker Yun; Chow, Marcus; et al.
Abstract: Introduction: Several small studies have reviewed the efficacy of abiraterone acetate plus prednisolone (AAP) in clinical practice outside a trial setting. We report the largest cohort study of clinical outcomes in metastatic castrate‐resistant prostate cancer (mCRPC) patients treated with AAP in a multicenter multiracial clinical setting. Methods: A retrospective analysis on mCRPC patients treated at four tertiary hospitals in Singapore from 2012 to 2017 was conducted. Disease characteristics, treatment outcomes, and adverse events were retrieved from electronic medical records. Primary clinical end‐point was overall survival (OS). A subset analysis of patients with various variables and OS curves were generated using the Kaplan–Meier method and compared using the log‐rank test. Results: Out of 200 patients with mCRPC treated with AAP, 163 (81.5%) patients were chemo‐naïve (CN) and 37 (18.5%) patients were postchemotherapy (PC), with the median age of 68 (34–87) and 65 (52–80) years, respectively. Median OS was 20.0 (95% CI, 18.3–22.9) and 10.5 months (95% CI, 1.1–40.5) for CN and PC cohorts, respectively. A subset analysis of 108 patients showed a significantly longer OS in patients who had prior ADT for more than 12 months in CN patients ( P < 0.001). Incidences of G3/G4 events were around 6.6%; most common side effect being hypertension with an incidence of 2.4%. Conclusions: Treatment of CN and PC patients with AAP was associated with a comparable OS and progression‐free survival to the reported series. Patients who were responsive to prior ADT of 12 months or more were associated with an improved OS.